ETNOBOTANI PERNIKAHAN ADAT SUKU DAYAK PESAGUAN HULU KABUPATEN KETAPANG - roberto siahaan; Togar Fernando Manurung; Siti Masitoh Kartikawati (Universitas Tanjungpura, 2022)
The upstream Pesaguan Dayak tribe in Tanjung Beulang Village, Tumbang Titi District, Ketapang Regency is an ethnic pesaguan who is still strong in the tradition of traditional marriage which is divided into 2, namely the Donor and Non-Sumbang traditional marriage. In collecting data, this research uses survey methods with interview techniques (Key person and Proposive Sampling), observation and herbarium. the results of this study Tanjung Beulang Village has a traditional institution, namely traditional elders from a village (Demong) who know about the unwritten rules in the community and there are also people who think they have advantages who are named Pesaroh (shaman). The plants used in discordant marriages are 19 species and 9 families and 7 species are not discordant and 5 families are the same plant species in the discordant custom. There are 19 types of plants for discordant traditional weddings and 9 families have 3 meanings, namely as offerings to spirits in dispelling bad luck on the bride, as a concoction in traditional blessings and as snacks during the wedding procession, while traditional weddings are not discordant there are 7 types of plants 5 families have 3 meanings, namely giving souvenirs or providing guests who have been present at the wedding, as an ingredient in traditional blessings and as snacks during the wedding procession.Keywords: Ethnobotany, Dayak Pesaguan, Traditional Wedding.AbstrakSuku Dayak pesaguan hulu di Desa Tanjung Beulang Kecamatan Tumbang Titi Kabupaten Ketapang merupakan etnis pesaguan yang masih kental akan tradisi pernikahan adat yang terbagi menjadi 2 yaitu pernikahan adat Sumbang dan Tidak Sumbang. Pada pengambilan data penelian ini mengunakan metode survey dengan teknik wawacara (Key person dan Proposive Sampling), observasi dan herbarium. hasil penelitian ini Desa Tanjung Beulang mempunyai kelembagaan adat yaitu tetua adat dari suatu Desa (Demong) yang mengetahui tentang aturan-aturan tidak tertulis dimasyarakat dan ada juga orang yang anggap memiliki kelebihan yang diberi nama Pesaroh (dukun). Tumbuhan yang digunakan dalam pernikahan adat sumbang berjumlah 19 spesies dan 9 famili dan tidak sumbang berjumlah 7spesies dan 5 famili merupakan jenis tumbuhan yang sama dalam adat sumbang. Tumbuhan untuk pernikahan adat sumbang ada 19 jenis dan 9 famili mempunyai 3 makna yaitu sebagai sesajen kepada roh halus dalam membuang sial pada pegantin, sebagai ramuan dalam pemberkatan adat dan sebagai cemilan pada saat prosesi pernikahan sedangkan pernikahan adat tidak sumbang terdapat 7 jenis tumbuhan 5 famili mempunyai 3 makna yaitu pemberian cindera mata atau membekali tamu yang telah hadir dalam pernikahan, sebagai ramuan dalam pemberkatan adat dan sebagai cemilan pada saat prosesi pernikahan. Kata Kunci: Etnobotani, Dayak Pesaguan, Pernikahan Adat.